Pengaruh Variasi Kecepatan Putar dan Sudut Kemiringan Poros Pisau Terhadap Kualitas Hasil Pemotongan pada Mesin Pemotong Daun Bibit Bawang Merah - Muhammad Adib Ibrohim; Agus Hariyono (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
In processing agricultural products, various machining equipment is often used. One kind of machine which is being used for the processing of agricultural crop is a shallot leaf cutting machine, used to prepare seeds ready for replanting. However, this process often results in imperfect cuts, leaving leaves that are too long, this condition can slow down the growth of the shallot seedlings. This research aims to determine the effect of rotational speed and inclination angle of the cutting knife shaft in achieving optimal quality of the size of the cutting residue. The data collection method was carried out by varying the value of the rotational speed of 900rpm, 1000rpm, and 1100rpm with knife shaft tilt angles of 8o, 11o, and 14o. Then the data obtained was processed using the desain of eksperimen factorial. The most optimal results obtained in this research were the results of the size of the remaining leaves from cutting which had the smallest average value at a rotational speed of 1100 rpm and a shaft tilt angle of 11o with an average remaining leaf from cutting of 10.207 mm, while the cutting results had The largest average value was found at a rotational speed of 1100 rpm and a shaft tilt angle of 8o with an average remaining leaf from cutting of 15.707 mm.